Working Paper 40: Developing anti-corruption interventions addressing social norms: Lessons from a field pilot in Tanzania (Basel Institute on Governance Working Papers, 2022)
This Working Paper provides guidance on developing anti-corruption interventions based on a Social Norms and Behaviour Change (SNBC) approach. Still a relatively nascent field, SNBC interventions typically address social norms that make corruption acceptable or expected, and attempt to influence behaviours away from corrupt practices. The guidance is based on lessons learned from a largely successful pilot project in Tanzania that targeted social norms fuelling bribery ("gift giving") in health facilities and attempted to change the behaviours of both health care providers and users away from exchanging gifts. Survey results showed a 14–44% decrease in gift-giving intentions, attitudes and positive beliefs among hospital users following the pilot intervention.The guidance covers:How to identify when a SNBC approach is suitableEssential background research needed to design anti-corruption SNBC interventionsFrameworks to formulate theories of changeSpecific elements to build into SNBC interventionsWhat practitioners should expect when embarking on an SNBC interventionWays they can help build evidence and understanding of SNBC approaches in the anti-corruption field.About and acknowledgementsThis publication was supported by the Deutsche Gesellschaft für Internationale Zusammenarbeit (GIZ) GmbH on behalf of the Federal Ministry for Economic Cooperation and Development (BMZ). The contents of this publication do not represent the official position of either BMZ or GIZ.The pilot intervention that serves as the basis for most of the reflections included in this document was funded by the Global Integrity Anti-Corruption Evidence Programme (GI-ACE), funded with UK aid from the UK government.